Biofuels, Solar and Wind as Renewable Energy Systems - Pimentel, David (Springer, 2012)
This book examines various renewable energy technologies and reports on their potential to supply the United States and other nations with needed energy. Some chapters examine several renewable energy technologies and their potential to replace fossil fuel, while others focus on one specific technology and its potential, as well as its limitations. In this volume, the aim of the contributors is to share their analyses as a basis for more research in renewable energy technologies. Basic to all the renewable energy technologies is that they attempt to minimize damage to the environment that supports all life.